Salvinia auriculata supplementation reduces the deleterious effects of drought stress on sunflower seedlings - Souza, Janacinta Nogueira de (2021)
Low water availability in semiarid regions affects the development and productivity of agricultural crops. The work analyzed the effects of Salvinia auriculata application as a growth supplement and the activities of the antioxidative enzymes: superoxide dismutase, catalase, ascorbate peroxidase and guaiacol peroxidase on leaves and roots of sunflower seedlings submitted to hydric stress conditions. The experimental design was entirely randomized, arranged in 2x3 factorial arrangement, being two irrigation systems (irrigated and non-irrigated) x three substrates (sand; sand + commercial humus 80 kg N ha-1; sand + Salvinia auriculata 120 kg N ha-1), with eight repetitions. The supplementation with Salvinia auriculata provided higher increments in height, number of leaves and total fresh mass. In addition, there were increases in the activities of the antioxidative enzymes in leaves and roots of sunflower seedlings, deducing that the supplementation with the macrophyte S. auriculata minimized the deleterious effects of hydric stress on the growth of sunflower seedlings.